ANALISIS KINERJA KARYAWAN PADA PT PERINDUSTRIAN DAN PERDAGANGAN BANGKINANG - Hayatul Fadri; Zulfadil '; Taufiqurrahman ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT Perindustrian and Perdagangan Bangkinang located at M. Yamin Street Number 100. The purpose of this study to determine and analyze the influence of motivation and work environment simultaneously on employee performance. To identify and analyze the motivation and the working environment partially affect the performance of employee. To identify and analyze which variables are the dominant influence on the performance of employee at PT Perindustrian dan Perdagangan Bangkinang and to identify differences of performance of employee based on years of service at PT. Perindustrian dan Perdagangan Bangkinang. this research is analyzed using the Census. Methods of data analysis using simultaneous test and partial test (multiple linear regression analysis with SPSS version 21). The result showed that simultaneous motivation and work environment have a significant effect on the performance of employee. Motivation and work environment partially significant effect on the performance of employee.KeyWord : Motivation, Work Environment and Performance